Mosaicism in Stickler syndrome - Stevenson, David A. (2012)
Stickler syndrome is a heterogeneous condition due to mutations in COL2A1, COL11A1, COL11A2, and COL9A1. To our knowledge, neither non-penetrance nor mosaicism for COL2A1 mutations has been reported for Stickler syndrome. We report on a family with two clinically affected sibs with Stickler syndrome who have clinically unaffected parents. Both sibs have a novel heterozygous mutation in exon 26 of COL2A1 (c.1525delT); this results in a premature termination codon downstream of the mutation site. One parent was found to have low level mosaicism in DNA extracted from whole blood. This scenario encourages consideration of molecular testing in seemingly unaffected parents for recurrence risks and potential screening for mild age-related manifestations.